Crop Genetics - Suza, Walter; Lamkey, Kendall (Open textbook library., 2023)
This book provides an introduction to genetic concepts such as reproductive systems, recombination, mutation, segregation and linkage analysis, inbreeding, quantitative inheritance, fertility regulation, population genetics and polyploidy.